Tax Administration Reforms in the Caribbean : Challenges, Achievements, and Next Steps - Schlotterbeck, Stephane (Washington, D.C. : International Monetary Fund, 2017)
Over the past decade, governments in the Caribbean region have introduced the value-added tax (VAT) to modernize their tax system, rapidly mobilize revenue and reduce budget deficits. This paper analyzes VAT performance in the region and concludes that while it has boosted revenues, the VAT has not reached its potential. Intended as a broad-based tax with limited exemptions, a single rate and zero-rating confined to exports, the VAT's design often lacks these characteristics. The paper also finds that although tax administration reforms can boost revenues, countries have just started to address organizational inefficiencies, data integrity issues, and operational ineffectiveness. These reforms need to intensify in order to have a more significant impact on compliance and revenue.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet